A Personal Leadership Statement (2023)
This study determines the conditions by which leadership empowerment is a necessity for the field of education. In order to reach or achieve empowerment during the teaching and learning leadership of the apprentices, teachers need to start making their own cooperative decisions based on the given resources in order to take the risk of improving, enriching, and developing new proposals based on the diversity found in the educational environment. This paper focus on highlighting the importance of being an empowered teacher leader in the classroom. This guided course provided all of us with the necessary qualities and characteristics to recognize our main factions as leaders, and also how to use these characteristics to positively influence the educational system in our environment. This leadership statement proposes the need that every teacher needs to take part in leadership empowerment.